A Corporate Model of Similitude for SMEs Reunion into a Corporation, Viewed from the Angle of Physical Thought, and Its Complex Economic and Social Impact - Gheorghe Săvoiu; Constantin Manea; Victor Iorga Simăn; Florentina Magda Enescu; Mladen Čudanov (Amfiteatru Economic Journal, 2011)
In order to exceed the circularity of formal economic thinking, the authors of the present paper favour the models of thinking specific to physics, which are also constructed statistically and mathematically, in an attempt to find an answer to the reunion of similar small and medium enterprises (SMEs), into multinational corporations. A model based on the theory of similitude is thus made use of, born from the very essence of physics, and having an economic and social destination and a complex impact. The physical models intended for economic systems are expressed as systems of partial differential equations, and the result becomes a new vision of reality. This paper details an original model based on physical similitude for SME amalgamation under the name of multinational corporations. After an introduction to the physical theory of similitude, the first section describes the physics model because of the reunion of similar SMEs. The real birth of some corporations in Serbia forms the content of the second section; the economic and social phenomena relating to the generation of such corporations, and the corporate social responsibility are emphasized. The idea of social complexity and its impact as the fifth dimension of a modern multinational corporation conclude the paper.
Keywords: C65; M10; M13; M14; 330; physical model; small and medium enterprise (SME); multinational corporation (MNE); corporate social responsibility (CSR); economic and social complexity